PENYULUHAN DIABETES MILITUS PADA WUS DI LINGKUNGAN WILAYAH KERJA PUSKESMAS BINJAI KOTA TAHUN 2023 - Ningsih, Fifi Ria; SINAGA, BD. ELIZA BESTARI (Universitas Aufa Royhan Di Kota Padangsidipuan, 2023)
According to data (WHO, 2022), around 422 million people in the world suffer from diabetes mellitus. Based on data published by the World Health Organization (WHO), diabetes will be one of the top 10 causes of death worldwide in 2022. The majority of type 1 diabetes sufferers in Indonesia are aged between 20-59 years. However, there are also quite a lot of young sufferers, as can be seen in the graph. The method for implementing PKM activities is carried out in the Binjai City Community Health Center Work Area, PKM implementation is carried out at WUS. On Friday and Saturday, December 1 – 2 2023. Factors that cause diabetes mellitus include genetics, hereditary factors play an important role in the incidence of this disease. If parents suffer from diabetes mellitus, the chances of their children suffering from diabetes mellitus are greater. According to data on DM cases in Binjai in 2017, there were 1856 cases including in the Binjai City Health Center Work Environment area. Based on the problems above, the author is interested in carrying out the Diabetes Millitus Program outreach activities to WUS so that the public is more aware of the importance of preventing DM. According to data (WHO, 2022), around 422 million people in the world suffer from diabetes mellitus. Based on data published by the World Health Organization (WHO), diabetes will be one of the top 10 causes of death worldwide in 2022. The majority of type 1 diabetes sufferers in Indonesia are aged between 20-59 years. However, there are also quite a lot of young sufferers, as can be seen in the graph. The method for implementing PKM activities is carried out in the Binjai City Community Health Center Work Area, PKM implementation is carried out at WUS. On Friday and Saturday, December 1 – 2 2023. Factors that cause diabetes mellitus include genetics, hereditary factors play an important role in the incidence of this disease. If parents suffer from diabetes mellitus, the chances of their children suffering from diabetes mellitus are greater. According to data on DM cases in Binjai in 2017, there were 1856 cases including in the Binjai City Health Center Work Environment area. Based on the problems above, the author is interested in carrying out the Diabetes Millitus Program outreach activities to WUS so that the public is more aware of the importance of preventing DM.